A manner of correspondence : a study of the Scriblerus Club - Brückmann, Patricia Carr, 1932- (CEL - Canadian Publishers Collection., 1997)
"A Manner of Correspondence examines one of the most interesting of literary clubs - the Scriblerus Club - whose members were Jonathan Swift, Alexander Pope, John Gay, John Arbuthnot, Thomas Parnell, and Robert Harley, Earl of Oxford. Patricia Bruckmann shows that the Scriblerians were bound by correspondent values, complementary talents, and a united satiric program." "Tracing their shared vision in such works as Memoirs of Scriblerus, Travels into Several Remote Nations of the World, The Beggar's Opera, and The Dunciad, Bruckmann identifies the pastoral as their common ideal and analyses their shared hostilities and anxieties regarding the erosion of that ideal in an age they saw as grotesquely degenerate. She points out that in many ways the group was out of step with its own time and much more attuned to ancient and traditional images of felicity and to ancient authors who subscribed to these values. The influence of Erasmus and Sir Thomas More, who both figure as icons in the Scriblerians' work, as well as such authors as Seneca, Lucian, Lucius Apuleius, and Francois Rabelais is explored in detail." "Bruckmann highlights the Scriblerian influence on writers such as Henry Fielding, Lawrence Sterne, Vladimir Nabokov, John Barth, Robert Coover, and James Joyce, offering a place for dialogue between modern humanists and their eighteenth-century forebears."--Jacket